Immunogenicity assay development and validation for biological therapy as exemplified by ustekinumab. (3rd February 2019) - Mojtahed Poor, S; Ulshöfer, T; Gabriel, L A; Henke, M; Köhm, M; Behrens, F; Geisslinger, G; Parnham, M J; Burkhardt, H; Schiffmann, S
Summary: Introduction of biotherapeutics has been a major milestone in the treatment of different chronic diseases. Nevertheless, the immune system can recognize the administered biological as non-self and respond with generation of anti-drug antibodies (ADA), including neutralizing ADA (nADA). Immunogenic responses may result in altered drug dynamics and kinetics leading to changes in safety and efficacy. However, there are several challenges with standard techniques for immunogenicity testing. Ustekinumab (UST), used in different inflammatory diseases, is a therapeutic antibody directed against the shared p40 subunit of interleukin (IL)-12 and IL-23, interfering in the pathogenically crucial T helper type 1 (Th1)/Th17 pathway. We established and validated different approaches for detection and quantitation of UST, UST-specific ADA and nADA. Addressing the obstacle of complex formation of UST with nADA, we developed an acidification assay to approach the total amount of nADA. Validated methods were based on surface plasmon resonance spectroscopy (SPR), enzyme-linked immunosorbent assay (ELISA) and a cell-based approach to characterize neutralizing capacity of nADA. Parameters assessed were determination and quantitation limits, linearity, range, precision, accuracy and selectivity. Quantitation of ADA and UST was feasible at lower concentrations using ELISA, whereas SPR showed a wider linear range for determination of ADA and UST. Accuracy, precision and linearity for quantitation were comparable using ELISA, SPR and the cell-based approach. All validated parameters fulfill the requirements of regulatory agencies. A combination of the testing approaches could address the increasing demand of precision medicine as it can be suitable for capturing the whole spectrum of immunogenicity and is transferable to other biologicals.